Learning from tradition: The role of environment perception layers in space making. The case of the Persian Garden - Reza Ramyar (Journal of Urban Management, 2020)
Extensive geographical and temporal uses of a built environment with a unique characteristic and spatial pattern indicates timelessness qualities of the space. The organic qualities, which originated from within us and differentiated by inspiration from specific local ontology, have been perceived by different people in different periods of time. In order to identify the effectiveness of these environments, this paper studies and analyzes the Persian garden, which was made for recreation, was designed to fully engage the people, and respond to their spatial needs for the relaxation. This paper analyzed the Persian garden with local epistemological science and ancient literature to probe human understanding of space and to provide a model of the multi-layer perception of the environment, which helps us to understand the reason of why visitors perceive the environment appealing and to make effective use of these qualities in creating today spaces.
Keywords: 710; Garden layers; Human-space interaction; The Persian garden; Perception model